Pengendalian Persediaan Bahan Baku Tebu Di PG X (Forum Agribisnis, 2020)
Sugarcane is one of the plantation crops which is used as raw material for making sugar. The efficiency of inventory is very important for a sugar factory. The purpose of this study is to determine the order level, order frequency, the amount of safety stock (Safety Stock), re-order points (sugarcane raw material) which is economical and to know the total inventory cost (Total Inventory Cost) of sugarcane raw material economical in PG X. The method of determining the area of ​​this research was carried out intentionally (purposive). The research method uses the descriptive-analytic method. The analytical tool used is Economic Order Quantity (EOQ), Re-Order Points (ROP), Safety Stock (SS), and Total Inventory Cost (TIC). The results of the 2018 and 2019 EOQ calculations show it is not yet economical. The 2018 EOQ calculation was 1.688,79 tons greater than the number of orders made by PG X by 1.483,9 tons and the 2019 EOQ calculation was 3.074 tons greater than the number of bookings made by PG X by 976,6 tons. The value of the safety stock in 2018 amounted to 1.483,9 tons and in 2019 it was 976,6 tons. The value of ROP in the supply of raw sugar cane in 2018 was 2.967,8 tons and in 2019 it was 1.953,2 tons. The 2018 TIC value is Rp. 139.031.870 smaller than the cost of inventory incurred by the company of Rp. 158.302.102 and the 2019 TIC value of Rp. 208.014.632 less than the cost of inventory incurred by the company of Rp. 654.250.185. The results of the last two years calculations indicate the inefficiency of orders made because it causes the frequency of orders is greater and the inventory costs incurred by PG X are higher., so with economic calculations, the order frequency will be less and the total cost of inventory will be lower.